Study of Interface Adhesion Between Polyurethane and Aggregate Based on Surface Free Energy Theory and Molecular Dynamics Simulation - Zengping Zhang; Jiajun Ji; Xue Li; Zhongbao Shi; Junjie Wang (Applied Sciences)
In order to eliminate the negative effects caused by traditional pavements, permeable pavements are gradually being used in road construction. In recent years, polyurethane (PU) has been used as a new binder in permeable pavement mixtures. However, compared to traditional pavement mixtures, the adhesion properties between PU and aggregate have not been systematically analyzed. In addition, no clear standards have been established for the performance testing of PU mixtures, posing significant challenges for the selection of materials and the optimization of formulations for PU mixtures. Therefore, this paper proposes new methods for evaluating the performance of PU mixtures from a microscopic point of view, aiming at evaluating the adhesion properties between PU and aggregates. In this study, a PU binder was synthesized. The adhesion properties of this PU binder with aggregate were evaluated by surface free energy measurement and molecular dynamics (MD) simulation. Finally, the effects of different environmental conditions and aggregate types on the PU–aggregate adhesion properties were investigated. The results showed that the adhesion between PU and basalt is consistently better than that with limestone, although the adhesion between PU and aggregate decreased under acidic conditions. It implies that the PU–basalt mixture has better water resistance than the PU–limestone mixture. Furthermore, the results of the surface free energy measurements and MD simulations for the evaluation of adhesion at the PU–aggregate interface showed good correlation with the macroscopic performance experiments, which can be extended to the study of the adhesion properties of other materials.